On the question of ‘architectural copy’ in the Middle Ages - Schenkluhn, Wolfgang (Aesthetica Preprint, 2024)
The question of copying in medieval architecture only arises with the ability to complete a medieval building in the 19th century, which presupposes knowledge and mastery of the forms of past times. In the Middle Ages, the restoration of a building took place under the sign of its improvement or as a new construction in a more praiseworthy scheme, an adoption of older forms took place under the conditions of auctoritas, which led to the use of architectural quotations. Instead of copying, one should therefore speak of architectural appropriation or adoption. It characterizes a participatory relationship to the architectural model, as it builds on its significance and power and transfers it to the copy through formal adoption. A building located elsewhere and built at a different time will not be transferred in real terms, but rather made vivid in certain features through architecture. A building that can be physically experienced becomes an image of itself in reception, whereby the way it is shown is not external to the intention. The architectural quotation is the point of connection to the past and allows the power of authority to become visible. It is thus an essential factor of continuity.